Tribological Behavior of Hydrophilic and Hydrophobic Surfaces in Atmosphere with Different Relative Humidity - Kanao Fukuda (Japanese Society of Tribologists, 2019)
The significant influences of atmospheric humidity on tribological phenomena are widely recognized. Although the influencing mechanisms of the humidity have been studied for a long time, many of the previous explanations remain in the qualitative estimation of mechanisms particularly from chemical effects viewpoint. In order to elucidate how the adsorbed water on a surface influences tribological phenomena, the current authors conducted ball to ball scratch tests for austenitic stainless steel (JIS SUS304) and proposed the mechanisms from a physical/mechanical viewpoint. A singular phenomenon was found; a lateral force, which can be regarded as a friction resistance, at a downhill motion showed significantly higher value than that at an uphill motion. The phenomenon was hypothesized to be influenced by Laplace pressure effect at a meniscus formed due to adsorbed water on the surface. In this study, polytetrafluoroethylene (PTFE) as the hydrophobic material was tested in comparison with SUS304 to show that the adsorbed water layer causes the singular phenomenon. PTFE successfully prevented the singular phenomenon while SUS304 reproduced it. The equilibrium analysis of the ball showed that adsorbed water contributed to the increase of the coefficient of kinetic friction but not of negative normal force at the contact point of SUS304.